Emotional intensity and its relationship to moral imagination (among middle school) teachers (Journal of the College of Basic Education, 2025)
The research aims to identify emotional intensity and its relationship to moral imagination among middle school teachers. The researcher relied on the descriptive approach and chose a random sample of (224) middle school teachers in the center of Babel Governorate for the academic year (2023/2024). The researcher adopted the research tools and extracted the values ​​of validity and reliability for them using several statistical methods, including the t-test for two independent samples and one sample and Pearson's correlation coefficient. The researcher reached several results and came out with a set of conclusions, recommendations and proposals.